A Review on Blind Bolt Connection to Concrete Filled Hollow Section Under Static Load - Mohd Hatta, Siti Haisal; Abd Rahman , Norashidah (Recent Trends in Civil Engineering and Built Environment, 2021)
The use of hollow section columns in steel construction is presently hindered by the lack of adequate connection technologies. Research on the blind bolt is currently being extended to the use of CFHS to increase the overall strength of steel structures. However, information into blind bolted connection of concrete-filled hollow sections (CFHS) under static loading remains ongoing. The objectives of this study is to review on different type of bolt connection and to analyze the strength of the different type of blind bolt to CHFS under static load. The information is obtained from literature review through reading of journals, books, and other sources. The stiffness and ductility of the component is measured under static load test, and the main parameters that have been selected for investigation involve the diamater and grade of the fastener’s shank, and the strength of the concrete infill. Based on previous research the influence of important parameter in determine the strength of blind bolts, the bolt grade and diameter also had a significant influence on the stiffness and strength of the  blind bolts.